Development of Triple Representation Based on Virtual Lab Media on The Chemical Equilibrium Experiment in Online Learning Era - Rokhim, Deni Ainur; Septiani, Maya Oki (Journal of Educational Chemistry (JEC), 2021)
The implementation of chemistry practicum generally has several obstacles such as the lack of tools and materials as well as limited time and space causing students to have less understanding of the procedures and concepts learned in the practicum. This problem can be solved by utilizing a media called virtual lab which helps students prepare practicum activities independently. Virtual labs have the advantage of being able to provide performance to students in doing practical work in real laboratories, especially in chemistry learning process. This media can be improved in quality by integrating the triplet representation aspect which consists of three aspects, namely the macroscopic aspect (practicum technical skills), the submicroscopic aspect (the particulate level), and the symbolic aspect (interpreting data through the form of reaction equations or symbols based on observations). The purpose of developing this media is to produce a virtual lab media to support laboratory-based learning with the features mentioned above to make students become scientists with comprehensive understanding competencies and laboratory engineering skills. The virtual lab media product developed by using the Lee Owens development method which consists of five stages, namely assessment / analysis, design, development, implementation, and evaluation results in the results that the virtual lab based on triplet representations on chemical equilibrium material fulfills very feasible criteria to be used as a learning resource for students. The percentage of product eligibility as a learning media is 86.15% and in terms of material it is 85.71%. The results of small group trials in class XI students of SMAN 3 Sidoarjo showed that the virtual lab developed had met the very feasible criteria with an average percentage of 86.40%. The final result of this virtual lab has been revised based on comments and suggestions from validators and test subjects. Practically, the media that has been developed is very useful to support practicum learning